Profiling outpatient workload: practice variations between consultant firms and hospitals in south west England. Issue 3 (June 1997) - Faulkner, A C; Harvey, I M; Peters, T J; Sharp, D J; Frankel, S J
Abstract : OBJECTIVES: To describe the variation in outpatient new to old ratios between consultants and between providers for seven high volume specialties (four surgical, three medical). DESIGN: This was a descriptive study at consultant and provider unit level based upon patient administration system data from the South and West Regional Health Authority for the financial year 1992-93. Additional components of variance analysis was used to distinguish individual consultant effects from host institution effects. SETTING: The former South Western Regional Health Authority area from Gloucestershire to Cornwall. SUBJECTS: Altogether 345 consultant firms in seven specialties grouped into 13 provider unit groups. MAIN MEASURES: New to old ratio, omitting elective inpatients followed up as outpatients. RESULTS: Variation between consultants is greater in surgical than in medical specialties, while absolute levels of new to old ratios tend to be higher in surgical specialties than in medical. Variation between provider unit groups is also greater in surgical specialties. Analysis of variance shows that more total variance is attributable to provider unit group in gynaecology than in other specialties. CONCLUSIONS: Within individual specialties there is evidence of substantial variation that is not attributable to underlying differences in morbidity patterns. There is evidence of marked variation in terms of both individual consultants and institutions, a finding that provides the springboard for further analytical work. Published routine outpatient activity statistics should distinguish between new referrals, inpatient follow up, and clinic rebookings.